2015
DOI: 10.1161/circimaging.114.002954
|View full text |Cite
|
Sign up to set email alerts
|

18 F-Florbetapir Binds Specifically to Myocardial Light Chain and Transthyretin Amyloid Deposits

Abstract: Background 18F-florbetapir is a promising imaging biomarker for light chain (AL) and transthyretin (ATTR) cardiac amyloidosis. Our aim, using human autopsy myocardial specimens, was to test the hypothesis that 18F-florbetapir binds specifically to myocardial AL and ATTR amyloid deposits. Methods and Results We studied myocardial sections from 30 subjects with autopsy documented AL (N = 10), ATTR (N = 10) and non-amyloid controls (N = 10), using 18F-florbetapir and cold florbetapir compound and digital autora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 19 publications
3
55
0
1
Order By: Relevance
“…Recent studies have shown that it is also taken up in the heart in patients with ATTR-CA and AL-CA (Figure 3, lower right panel). Similar findings have been reported for another beta amyloid imaging agent 11C-PiB 89 . These agents hold promise for absolute quantification of amyloid burden.…”
Section: Diagnosing Cardiac Amyloidosissupporting
confidence: 89%
“…Recent studies have shown that it is also taken up in the heart in patients with ATTR-CA and AL-CA (Figure 3, lower right panel). Similar findings have been reported for another beta amyloid imaging agent 11C-PiB 89 . These agents hold promise for absolute quantification of amyloid burden.…”
Section: Diagnosing Cardiac Amyloidosissupporting
confidence: 89%
“…(18)F-florbetapir myocardial uptake was elevated in 9/9 patients with CA (4 ATTR-CA, 5 AL) but not in amyloid-negative controls [57]. An autopsy study showed that all myocardial sections of patients with CA (10 ATTR-CA, 10 AL) had elevated uptake of (18)F-florbetapir compared to controls [58]. (18)F-florbetaben also localized to myocardial amyloid fibrils in 10 patients with CA (5 ATTR-CA, 5 AL) with no uptake seen in 4 controls with LVH secondary to longstanding hypertension [59].…”
Section: Diagnosismentioning
confidence: 99%
“…The authors concluded that the presence and type of ATTR mutation may influence (18)Na-F tracer uptake [68]. A recent study of (18)F-florbetapir uptake in myocardial autopsy specimens (10 AL, 10 ATTR, 10 controls) found increased uptake in all CA patients and no controls, with uptake greater in AL than ATTR [58], while another study demonstrated increased liver uptake of (18)F-florbetapir in AL and normal liver uptake in ATTR-CA [69], suggesting that (18)F-florbetapir may preferentially bind AL fibrils.…”
Section: Subtypingmentioning
confidence: 99%
“…3 Physician education, along with now widely accessible assays for diagnosis and monitoring (such as the Freelite ® serum free LC assay) as well as improved cardiac imaging have contributed to the increase in diagnosis. In addition to ultrasound echocardiography and late gadolinium enhancement (LGE) by cardiac MRI, 4 newer imaging modalities with 99m Tc-pyrophosphate 4, 5 and florbetapir 6 have improved detection, monitoring of disease progression, and treatment response in cardiac amyloidosis. With these imaging modalities becoming more widely accessible, it is likely the identification of cardiac amyloidosis will only continue to increase.…”
mentioning
confidence: 99%